De novo deletion of Xp22.2-pter in a female with linear skin lesions of the face and neck, microphthalmia, and anterior chamber eye anomalies. Issue 1 (January 1990) - Temple, I K; Hurst, J A; Hing, S; Butler, L; Baraitser, M
Abstract : A female infant is described with an unusual combination of eye and skin findings. Raw linear skin lesions on the face and neck were present at birth, healing to leave pigmented streaks. In addition she had left sided microphthalmia and bilateral sclerocornea. Chromosome analysis showed a terminal deletion of the short arm of the X chromosome (Xp22.2–pter). Clinical findings were similar to three previously described children with translocations involving Xp22.3. The condition probably represents a new syndrome distinct from incontinentia pigmenti and Goltz syndrome.